Memperkuat Ideologi Kebangsaan Melalui Perdamaian di Indonesia - Teguh Prasetyo (PAX HUMANA, 2015)
This paper discusses how to strengthen cultural value that comes form the soul of Indonesian (political) nation (Volkgeist). This national value are universal and noble, and at the same time it also must harmonius with the law in Indonesia. Peace also emerge as one of the supporting value which could amplify constitutional and law practices. To achive it intention, this paper utilize Dignified Justice Theory which influenced from Indonesian wisdom and practices to analyze those values. This paper conclude that law enforcement in Indonesia must accelerate itself in order to uphold peace and unity of the nation, and actualize constitutional promises Keywords: Peace, National Value, Law